Analisis Penambahan Ion Na dan Ca pada Hidrolisis Pati Singkong (Manihot esculanta) untuk Meningkatkan Aktivitas Enzim: Studi Kinetika Hidrolisis - Hargono Hargono; Bakti Jos; Hantoro Satriadi; Muhammad Fahmi Zakaria (Diponegoro University, 2022)
Sweet cassava is tuber that contains large amount of starch so that it can produce reducing sugars. The addition of metal ions can increase enzyme activity. The purpose was to study the addition of Na and Ca ions on reducing sugars concentration and to study the hydrolysis kinetics. Experiments were carried out at various concentrations of substrates (100, 200, and 300 g/L), enzyme concentrations (1 and 1.5% (w/w)), addition of Na and Ca ions of 60 ppm. The hydrolysis method was conducted at temperature of 30°C with the enzyme StargenTM 002 at pH 4, for 24 hours. The results showed that starch concentrations of 100-200 g/L were able to significantly increase the reducing sugars at enzyme concentration of 1.5% (w/w). The addition of Ca ions increased the concentration of reducing sugar by 64% while the addition of Na ions increased it by 18.9%. The best reducing sugar concentration (68.79 g/L) was obtained at starch concentration of 200 g/L and enzyme concentration of 1.5% (w/w) with the of Ca ions. Kinetic studies show that phenomenon follows Michaelis-Menten equation with Vmax valued of 6.053; 8,881; 15.106 g/L.hour, respectively. So that, addition of Na and Ca ion can increase the enzyme activity